PERAN MEDIA MASSA NASIONAL DALAM POLITIK INTERNASIONAL - Andrianti, Nita (Informasi, 2015)
AbstractIn international politics, the mass media is not only a source of political information but also trigger the occurrence of political change. In general, the mass media has a specific tendency for reporting international coverage of the political events. In short, the media has a major role in the international political communication. Active involvement of the media have spawned the term "media diplomacy", the mass media as a channel in a diplomatic mission of a state against another state. As "media diplomacy", the mass media not only report diplomatic events, but also act as negosiator.Related to the media diplomacy that the media as one of the actors in the dynamic system of international relations. Indonesia's position in the system of international relations greatly influenced the mass media actors.AbstrakDalam politik internasional, media massa bukan hanya sumber informasi politik, tetapi juga kerap menjadi pendorong terjadinya perubahan politik. Secara umum media massa memiliki kecenderungan--kecenderungan tertentu dalam melakukan liputan pada peristiwa politik internasional. Dalam wujud yang lebih konkret, media memiliki peranan besar dalam komunikasi politik internasional.Keterlibatan aktif media ini telah melahirkan istilah "media diplomacy' artinya media massa sebagai saluran dalam menjalankan misi diplomasi sebuah negara tehadap negara lainnya. Sebagai "media diplomacy", media massa tidak hanya sekadar meliput peristiwa diplomatik, tetapi media massa harus memiliki sikap sebagai seorang negosiator.Terkait dengan media diplomacy bahwa media sebagai salah satu aktor dalam dinamika tata hubungan internasional. Posisi Indonesia dalam tata hubungan internasional sangat dipengaruhi aktor media massa tersebut.Keywords: Mass Media, Internasional, Politic Communication, Diplomacy.